Psychiatric adverse reactions to non-selective RET multi-kinase inhibitors: a large-scale pharmacovigilance analysis - Wang, Xuyan; Yin, Donghong; Tang, Yang; Xiao, Feng; Wang, Shuyun (Frontiers in Pharmacology, 2023)
Objective: The development of non-selective multi-kinase inhibitors (MKIs) has improved the. survival outcomes of patients with cancers. Psychiatric disorders represent an MKIs related AE of particular concern, as they are often ignored and may harm the patient’s personal and social functioning. Therefore, we use the public database to describe and evaluate psychiatric adverse events related to various non-selective RET MKIs. Provide evidence for optimizing drug administration in the clinic. Methods: We analyzed spontaneous reports submitted to the Food and Drug Administration Adverse Events Reporting System FDA Adverse Event Reporting System in an observational and retrospective manner. Selecting psychiatric AEs to non-selective RET multikinase inhibitors (sorafenib, lenvatinib, vandetanib, cabozantinib, and sunitinib). We used Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) algorithms to analyze suspected adverse reactions of psychiatric related induced by non-selective RET MKIs between January 2004 and September 2022. Results: As of September 2022, 1,108 non-selective RET MKIs ICSRs were related to psychiatric AEs. 706 were ADR ICSRs, and 402 were non-ADR ICSRs. There were more ADR cases in males (69.5%), and 71.8% of the cases were submitted from North America. The age group most frequently affected by psychiatric ADRs was individuals aged 50–64 years for sorafenib, whereas 65–74 years for sunitinib, cabozantinib, and lenvatinib. In all psychiatric ADRs ICSRs, excluding missing data (n = 329), the most common adverse outcome was hospitalization (260/377, 69.0%), and the most serious was death (100/377, 26.5%). What calls for special attention is that the percentage of death rate for sunitinib was highest (24/54, 44.4%) in sunitinib-related psychiatric ADRs ICSRs, (excluding missing data, n = 44), followed by lenvatinib (4/14, 28.6%). Based on ROR, PRR, BCPNN, and MGPS methods, sorafenib, sunitinib, cabozantinib, and lenvatinib are significantly associated with all ADRs, the strongest association was the association between cabozantinib and feeding disorder. Conclusion: Despite the limitations, our study found that, except for vandetanib, other four drugs have been reported to have significant psychiatric side effects. Clinicians need to recognize and monitor these potentially fatal adverse events. If it is suitable for treatment with vandetanib, doctors should choose vandetanib for treatment.